Desenvolvimento de um equipamento para análise de desgastes em prótese de articulação total de quadril - Haddad, Michel [UNESP] (2015)
The increase of Brazilian income coupled with the increase in life expectancy, along with other factors, led to the conditions for the rise of demand for surgeries of total hip joint prosthesis. The absence of a regulatory standard for the minimum durability of these prostheses did arise on the market a great variety of products that do not meet minimum requirements of use, causing large numbers of unsuccessful surgeries and bringing patients disorders. The tests for verification of the durability of prosthetics carried out in national territory using, for the most part, imported equipment, with a high degree of sophistication, making them high cost. Being the Sistema Único de Saúde (SUS) the largest purchaser of these prostheses, it becomes impossible to maintain a routine tests in order to evaluate the quality of the product to be purchased and offered to patients. The design and assembly of a viable equipment in stages of manufacturing, operation and maintenance aims to meet this demand with greater scope, providing affordable tests. Meet the specific standards, with some adjustments, made the operation of the equipment and the analysis of specimens of prostheses, which proved the feasibility of the project and its degree of care the need of Brazilian reality. It was conducted a test performed with a prosthetic assembly for a period of 12 days, totalizingng 1 million cycles. At the end, it was obtained the mass wear of the acetabular component in polymer, and it has been calculated the wear factor (K). The simulator showed proper functioning, produced the prescribed load profile by Technic Norm and the wear factor obtained was considered appropriate